Poland : Development of Capital Markets and Pension Funds - World Bank Group (World Bank, Washington, DC, 2019)
Poland’s capital markets can play a crucial supporting role to the ongoing economic development and efficient allocation of credit. Capital markets will become increasingly important to meet the long-term funding needs of strategic sectors, including large, medium and small entities. Expansion and diversification of capital market instruments and hedging tools will also be essential to provide adequate investment and risk management vehicles to much needed long-term savings. While capital market offers different sources of financing, this note focuses primarily on the fixed income markets. This technical note is structured as follows. Section II covers each of the main market segments, including money markets, government and non-government bond markets and derivatives markets. Section III provides an examination of the investor base, the current participation of the different investor segments in the bond markets, and recommendations to reach broader and more effective investor diversification. The Section IV is focusing on the critical reform of the Employee Capital Plan (PPK), as one critical group of institutional investors.